2016
DOI: 10.4236/ojo.2016.66023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mild to Moderate Hallux Valgus, Percutaneous Osteotomy versus Distal Chevron Osteotomy

Abstract: Objective: The aim of this study was to compare two different surgical techniques for treating mild to moderate cases of hallux valgus. Methods: Forty-one patients (58 feet) with mild to moderate hallux valgus were treated by either percutaneous technique (n = 24) patients (33 feet) or by distal chevron osteotomy (n = 17) (25 feet). Results: In the percutaneous group, after a mean follow up of 49.36 months, the mean correction of hallux valgus angle (HV) was 26.69˚; in the intermetatarsal angle, average correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Among the included studies, 8 studies ( 15 , 17 , 24 , 26 , 28 , 29 , 31 , 35 ) were RCTs, 2 studies ( 4 , 14 ) were prospective comparative studies, and 12 studies ( 5 , 13 , 16 , 18 , 22 , 23 , 25 , 27 , 30 , 32 34 ) were retrospective comparative studies. A total of 10 studies ( 13 , 17 , 22 28 , 32 ) reported on the 2G percutaneous hallux valgus surgery, in which 7 studies ( 13 , 22 25 , 28 ) involved Bösch osteotomy and 3 studies ( 17 , 26 , 27 ) involved a simple, an effective, a rapid, and an inexpensive (SERI) technique. Roth et al ( 22 ) conducted a retrospective comparative study to compare between Bösch and Kramer osteotomies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 8 studies ( 15 , 17 , 24 , 26 , 28 , 29 , 31 , 35 ) were RCTs, 2 studies ( 4 , 14 ) were prospective comparative studies, and 12 studies ( 5 , 13 , 16 , 18 , 22 , 23 , 25 , 27 , 30 , 32 34 ) were retrospective comparative studies. A total of 10 studies ( 13 , 17 , 22 28 , 32 ) reported on the 2G percutaneous hallux valgus surgery, in which 7 studies ( 13 , 22 25 , 28 ) involved Bösch osteotomy and 3 studies ( 17 , 26 , 27 ) involved a simple, an effective, a rapid, and an inexpensive (SERI) technique. Roth et al ( 22 ) conducted a retrospective comparative study to compare between Bösch and Kramer osteotomies.…”
Section: Resultsmentioning
confidence: 99%
“…Poggio et al ( 27 ) conducted a retrospective study to compare between the SERI technique and open scarf technique for hallux valgus. Othman and Hegazy ( 28 ) performed a RCT to compare between Bösch surgery and open Chevron osteotomy. Choi et al ( 13 ) performed a retrospective comparison between the Bösch technique and Chevron surgery.…”
Section: Resultsmentioning
confidence: 99%
“…1 The investigations in this meta-analysis were either second or third-generation techniques. 1,[16][17][18] Although these findings established a benefit to utilizing minimally invasive techniques compared with open, a large variation of minimally invasive techniques was seen within the analysis. Although the chevron and akin osteotomies are the staple of the third-generation minimally invasive the abundance of techniques described in the literature highlights the difficulty that may be encountered when attempting to achieve strong fixation with the chevron osteotomy.…”
Section: Possible Concerns Future Of the Techniquementioning
confidence: 98%
“…The ethology of HV is complex and multifactorial and might be caused by wearing improper footwear, abnormalities in foot anatomy and foot biomechanics, limb inequality, inflammatory joint diseases and genetic factors [ 8 ]. HV may lead to limitation of physical activities and foot pain [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%